1992
DOI: 10.1111/j.1476-5381.1992.tb14433.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of cyclic GMP formation to KRN2391‐induced relaxation in coronary artery of the pig

Abstract: 1 In the present study, we investigated the relationship between relaxation and guanosine 3':5'-cyclic monophosphate (cyclic GMP) formation induced by KRN2391, compared with those induced by nicorandil and nitroglycerin, in the coronary artery of the pig. 2 KRN2391 (10-8-3 x 10-5 M), nicorandil (10-8-3 x 10-4 M) and nitroglycerin (10-9-10-5 M) antagonized the contraction caused by 25 mM KCI in a concentration-dependent manner. 3 The concentration-relaxation curves for KRN2391, nicorandil and nitroglycerin shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

1993
1993
1997
1997

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…It is also reported that cromakalim has no appreciable effect on cyclic GMP level in rabbit mesenteric artery (17). Although it remains un clear whether KRN2391 produces an increase in cyclic GMP level in canine cranial mesenteric artery, we have re cently observed that KRN2391 increased the cyclic GMP level in porcine large coronary artery (8).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…It is also reported that cromakalim has no appreciable effect on cyclic GMP level in rabbit mesenteric artery (17). Although it remains un clear whether KRN2391 produces an increase in cyclic GMP level in canine cranial mesenteric artery, we have re cently observed that KRN2391 increased the cyclic GMP level in porcine large coronary artery (8).…”
Section: Discussionmentioning
confidence: 53%
“…In isolat ed canine large coronary artery, the relaxation caused by KRN2391 is antagonized by methylene blue, an inhibitor of soluble guanylate cyclase (6), but not by glibenclamide (7). Recently, Jinno et al (8) have observed that KRN2391 increased the cyclic GMP level in porcine coro nary artery. Nicorandil as well as KRN2391 is also report ed to show such a dual mechanism of action as a K chan nel opener and a nitrate (9,10).…”
mentioning
confidence: 99%
“…The vasodilating effect of KRN2391 has been shown to be due to its potassium channel opening action, because KRN2391 produces an increase in the efflux of 86Rb, which is used as a marker for potassium, in isolated rat aorta [1]. Further, KRN2391-induced relaxation of isolated aorta is partly inhibited by methylene blue and oxyhemoglobin [8], suggesting that KRN2391 may possess in part a nitrate-like vasodilating action in the aorta. Although potassium channel opening is considered to be a major mechanism of the vasodilating effect of KRN2391, the activation of guanylate cyclase due to this agent is mediated in a manner characteristic of nitrovasodilators because of the presence of the nitrate moiety within its structure.…”
Section: Discussionmentioning
confidence: 96%
“…Actually, KRN2391 as well as nicorandil is sug gested to show a K-channel opening action in resistive coronary arterioles of dogs because the increases in coro nary blood flow induced by intravenous administration of KRN2391 and nicorandil were inhibited by glibenclamide (2). In addition, Jinno et al (10) reported that KRN2391 produced an increase in cyclic GMP formation in porcine large coronary arteries, suggesting the nitrate action of KRN2391. Therefore, it is considered that KRN2391 and nicorandil show a K-channel opening action in addition to a nitrate action in proportion to the size of coronary ar tery.…”
Section: Discussionmentioning
confidence: 99%
“…In the coronary vascular bed, it has been demonstrated that the vasodilating action of nicorandil depends on the segment of coronary artery; i.e., nicorandil acts as a nitrate in large conductive coronary arteries (7) and as a K-channel opener in resistive coronary arterioles (8,9). One of the authors of this paper reported that KRN2391 increased cyclic GMP formation in porcine large coronary artery (10), suggesting a nitrate-like action of KRN2391 in por cine coronary arteries. In experiments using anesthetized dogs, the increase in coronary blood flow induced by the intravenous administration of KRN2391 was also inhibit ed by glibenclamide, suggesting that K-channel opening action contributes to the dilating effect of KRN2391 on resistive coronary arteries (2).…”
mentioning
confidence: 87%